Development of a supramolecular solvent-based extraction method for application to quantitative analyses of a wide range of organic contaminants in indoor dust - Marcinekova, Paula; Melymuk, Lisa; Bohlin-Nizzetto, Pernilla; Martinelli, Erika; Jílková, Simona Rozárka; Martiník, Jakub; Šenk, Petr; Kukučka, Petr; Audy, Ondřej; Kohoutek, Jiří; Ghebremeskel, Mebrat; Håland, Alexander; et al. (Analytical and bioanalytical chemistry, 2024)
This study investigates the efficacy of supramolecular solvent (SUPRAS) in extracting a diverse spectrum of organic contaminants from indoor dust. Initially, seven distinct SUPRAS were assessed across nine categories of contaminants to identify the most effective one. A SUPRAS comprising Milli-Q water, tetrahydrofuran, and hexanol in a 70:20:10 ratio, respectively, demonstrated the best extraction performance and was employed for testing a wider array of organic contaminants. Furthermore, we applied the selected SUPRAS for the extraction of organic compounds from the NIST Standard Reference Material (SRM) 2585. In parallel, we performed the extraction of NIST SRM 2585 with conventional extraction methods using hexane:acetone (1:1) for non-polar contaminants and methanol (100%) extraction for polar contaminants. Analysis from two independent laboratories (in Norway and the Czech Republic) demonstrated the viability of SUPRAS for the simultaneous extraction of twelve groups of organic contaminants with a broad range of physico-chemical properties including plastic additives, pesticides, and combustion by-products. However, caution is advised when employing SUPRAS for highly polar contaminants like current-use pesticides or volatile substances like naphthalene.